Teologi Luka: Protes, subversi, dan harapan dalam Mazmur 37 - Karel Martinus Siahaya (KURIOS, 2024)
This study analyzes Psalm 37 through the lens of liberation hermeneutics, the theology of suffering, and Midrash Tehillim. The findings reveal that the promise of land inheritance for the righteous is not merely an eschatological comfort but a subversive social critique against structures of injustice. The acrostic structure emphasizes God’s order amid social chaos, while Midrash Tehillim teaches that theological protest is a valid expression of faith. The suffering of the righteous is understood as part of God's solidarity, who shares in humanity’s pain. Thus, Psalm 37 calls the church to become an empathetic agent of change, embodying social justice and strengthening believers’ faith. This message is relevant to modern contexts marked by social and economic inequality. This research highlights that experiences of suffering are not just pain, but also a call to action, involving participation in God’s mission of peace and justice in a broken world.   Abstrak Penelitian ini menganalisis Mazmur 37 dengan pendekatan hermeneutika pembebasan, teologi luka, dan Midrash Tehillim. Hasil penelitian menunjukkan bahwa janji pewarisan tanah bagi orang benar bukan hanya penghiburan eskatologis, melainkan kritik sosial subversif terhadap struktur ketidakadilan. Struktur akrostik menegaskan keteraturan Allah di tengah kekacauan sosial, sementara Midrash Tehillim mengajarkan bahwa protes teologis adalah bentuk iman yang sahih. Penderitaan orang benar dipahami sebagai bagian dari solidaritas Allah yang turut merasakan penderitaan umat. Dengan demikian, Mazmur 37 mengundang gereja untuk menjadi agen perubahan yang empatik, menghadirkan keadilan sosial dan meneguhkan iman umat. Pesan ini relevan bagi konteks modern yang sarat dengan ketimpangan sosial dan ekonomi. Penelitian ini menegaskan bahwa pengalaman luka bukan sekadar penderitaan, tetapi juga panggilan untuk bertindak menghadirkan damai sejahtera Allah di tengah dunia yang penuh ketidakadilan.